Pengaruh Konstitusi Timor Leste terhadap Perlindungan Hak Asasi Manusia dalam Konteks Pascakonflik - Carolina da Cruz; Luzidia Dias Quintas (Jurnal Interpretasi Hukum, 2025)
Human Rights or abbreviated as HR are a set of rights inherent in the nature and existence of humans as creatures of God Almighty and are His gifts which must be respected, upheld and protected by the state, law and government, and every person for the sake of human honor and dignity. This study applies normative research methods and literature studies. The main focus of this study is on legal texts, journals and published documents. The approach method in this research uses a statutory approach which will be applied in this study to analyze various relevant legal regulations. The author uses a qualitative descriptive analysis method. Based on the results of this study, the Constitution of Timor Leste provides a fundamental influence in the protection of human rights through the establishment of basic principles of the rule of law and strong guarantees of human rights, which are very important in the post-conflict context to rebuild a just and stable society. The main challenges in implementing human rights guarantees contained in the post-conflict Timor Leste Constitution are rooted in limited law enforcement capacity, unresolved cases of past human rights violations, and socio-economic problems such as poverty.